2018
DOI: 10.1039/c7md00578d
|View full text |Cite
|
Sign up to set email alerts
|

Design, synthesis and biological evaluation of 3′,4′,5′-trimethoxy flavonoid benzimidazole derivatives as potential anti-tumor agents

Abstract: A series of 3',4',5'-trimethoxy flavonoids with benzimidazole linked by different chain alkanes have been designed and synthesized. The potential activity of these compounds as anti-tumor agents was evaluated by cytotoxicity assay in MGC-803 (human gastric cancer), MCF-7 (human breast cancer), HepG-2 (human hepatoma) and MFC (mouse gastric cancer) tumor cell lines. Among them, compound 7-(3-(2-chloro-1-benzo[]imidazol-1-yl)propoxy)-2-(3,4,5-trimethoxyphenyl)-4-chromen-4-one displayed the most potent antiprolif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 29 publications
0
9
0
Order By: Relevance
“…It is reported that G1 period and S period are preparing for the presynthesis of RNA and synthesis of DNA, respectively (31). The regulation of the cell cycle is necessary to cell proliferation (33). It was found that APS exhibited an anti-proliferative effect on cancer and displayed differentiation induction on erythroid (34).…”
Section: Discussionmentioning
confidence: 99%
“…It is reported that G1 period and S period are preparing for the presynthesis of RNA and synthesis of DNA, respectively (31). The regulation of the cell cycle is necessary to cell proliferation (33). It was found that APS exhibited an anti-proliferative effect on cancer and displayed differentiation induction on erythroid (34).…”
Section: Discussionmentioning
confidence: 99%
“…Further, the presence of an electron-withdrawing chlorine group in the imidazole ring of benzimidazole (the R 1 position) improved antiproliferative activity compared to the positioning of an electron-donating methyl group at the same place. 72…”
Section: Anticancer Potencymentioning
confidence: 99%
“…According to SAR results, chlorine (Cl) substitution at the R 1 position, rather than the R 2 and R 3 positions, of benzimidazole improved antiproliferative activity against all the cell lines tested. Further, the presence of an electron‐withdrawing chlorine group in the imidazole ring of benzimidazole (the R 1 position) improved antiproliferative activity compared to the positioning of an electron‐donating methyl group at the same place 72 …”
Section: Anticancer Potencymentioning
confidence: 99%
“…The core structure of benzimidazole is a vital pharmacophore at present. It has been used as a preferred scaffold for synthesizing selected drugs of interest in medicinal chemistry, including antimicrobial [ 39 , 40 ], analgesic [ 41 ], antihelmintic [ 42 , 43 ], antioxidant [ 44 ], antimalarial [ 45 ], antiviral [ 46 ], and anticancer [ 47 ] activity. Many benzimidazole-based derivatives are available as medicines such as bendamustine, veliparib, nocodazole, liarozole, and pracinosta.…”
Section: Benzimidazole Hybridsmentioning
confidence: 99%